Road pavement energy harvesting: A technological, economical and cost-benefit analysis. Issue 1 (31st December 2022) - Duarte, F.; Silva, A.; Barbosa, M.; Carvalho, L.
ABSTRACT: With the growing need for cleaner energy sources, research into the energy harvesting industry has increased over the last years. Roadways and transport infrastructure are promising contexts for energy harvesting due to their global coverage, being continuously exposed to everyday traffic-induced pressures. This study presents a model for Technical and Economic Analysis, as well as a Cost-Benefit Analysis model for Road Pavement Energy Harvesting systems. These models are then applied in a grid injection scenario, testing their applicability on a system developed by a startup company. Results show that the tested technology is economically viable for scenarios under subsidized regimes, but not yet for grid injection applications, suggesting the need for financial incentives in the field. However, it is argued that these systems hold major social and environmental value, enabling different types of business models that might increase stakeholders' motivation to invest.